MODEL LINEAR GOAL PROGRAMMING PADA PENJADWALAN PERAWAT UGD RUMAH SAKIT UMUM DAERAH KOTA SEMARANG - Ichsan, Nur; Dwijanto, Dwijanto; Arifudin, Riza (Universitas Negeri Semarang, 2016)
Scheduling of emergency room is quite a complicated issue for each hospital, including the RSUD Kota Semarang. Many methods can be used in the scheduling of nurses, including the Linear Goal Programming (LGP). The purpose of this study was to determine the form of the LGP model and comparison between manual scheduling and LGP model. The method used in this study is by changing the scheduling rules into a form of LGP models, then the model is solved with LINGO 14. In this model, the hospital rules should not be violated is called major constraints, while the rules may be violated at any time is called additional constraints. Additional constraints is a policy made by the head nurse to schedule in accordance with the conditions and needs of nurses. In this study there are 7 major constraints and 5 additional constraints. Based on calculations, obtained the nurse schedule for 31, 30, 29, and 28 days. From the analysis, LGP schedule for 31 days, 30 days, 29 days, and 28 days to meet all of the major constraints and additional constraints. While in manual schedule, the main constraints are met as much as 5 constraints. Then for the additional constraints are not met for all. From the analysis, LGP models can also be applied to the scheduling of nurses in the other room.